2021
DOI: 10.3390/biom11050759
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Sensing Element PDLIM5 Promotes Osteogenesis of Human Fibroblasts by Affecting the Activity of Microfilaments

Abstract: Human skin fibroblasts (HSFs) approximate the multidirectional differentiation potential of mesenchymal stem cells, so they are often used in differentiation, cell cultures, and injury repair. They are an important seed source in the field of bone tissue engineering. However, there are a few studies describing the mechanism of osteogenic differentiation of HSFs. Here, osteogenic induction medium was used to induce fibroblasts to differentiate into osteoblasts, and the role of the mechanical sensitive element P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The microfilament cytoskeleton formed by actin polymerization plays an important role in osteogenic differentiation of mesenchymal stem cells [ 50 ]. The arrangement of the microfilament cytoskeleton is significantly altered during osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The microfilament cytoskeleton formed by actin polymerization plays an important role in osteogenic differentiation of mesenchymal stem cells [ 50 ]. The arrangement of the microfilament cytoskeleton is significantly altered during osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…1 F) also improved with the prolongation of the osteogenic differentiation time, consistent with findings from our previous work. 5 Immunofluorescence additionally demonstrated that PDLIM5 co-localized with microfilaments ( Fig. S2B, C ).…”
mentioning
confidence: 88%
“…A study on the mechanism of osteogenic differentiation of HSFs found that depolymerization of microfilaments inhibited the expression of osteogenesis-related proteins and ALP activity of HSFs, whereas polymerization of microfilaments enhanced the osteogenic differentiation of HSFs. PDLIM5, a cytoskeleton-associated protein, can mediate osteogenic differentiation of fibroblasts by affecting microfilament formation and polymerization ( 85 ). Another study found that membrane-bound protein A2 promotes the ossification of ligament fibroblasts in patients with ankylosing spondylitis, and experiments suggest that it may function through the extracellular signaling-related kinase pathway ( 86 ).…”
Section: The Mechanism Of Fibroblast Regulating Fracture Healingmentioning
confidence: 99%